RIGHT-WING POPULIST REGIONAL MOVEMENTS IN GERMANY - A. E. Antonov; L. N. Korneva (Вестник Кемеровского государственного университета, 2017)
The article is devoted right-wing populist movements in Germany, which are the direct consequence of the crisis of multicultural community. In their propaganda they speculate on the mood in the society, using Islamophobia as their main weapon. The phenomenon of Islamophobia, or criticism of Islam, as well as the fight against its growing influence, has been heating up on the territory of the EU and, in particular, in Germany, where it is connected with Muslim immigrants. The right-wing movements bring the refugee issue into focus of public attention to strengthen their position in the current political landscape. The subject of the research is the most active and significant right-wing populist movements in modern Germany. The article defines the term of right-wing populism, as well as the most favorable conditions for its occurrence. The paper features the history, political activity and the ideology of the right-wing populist movements in Germany. It also offers a brief outlook on the degree of influence of anti-Islamic attitude in the European and German society.